Comparative Analysis of Boost and Hybrid Boost Converters - Romero-Carvajal, Ana Maria; Muñoz-Galeano, Nicolas; Lopez Lezama, Jesus Maria (Ingeniería, 2023)
Context: In power electronics applications, it is important to make comparisons between converters to choose the device that best suits a particular application. This paper compares the Boost converter and the hybrid Boost converter. The operating models of both converters under study are developed and explained in detail to allow for a proper comparison and analysis. Method: Using the passive sign law, the differential equations that govern the behavior of each converter are determined upon the basis of their switching states. Then, circuit simulations are performed by using the OpenModelica software to analyze the output signals of both converters with the same input parameters. Results: Comparisons of voltage and current gains, current and voltage time response, and ripple were obtained. Additionally, the efficiency was analyzed by adding resistive losses in each passive element of both converters. Conclusions: For high duties, the hybrid Boost converter has a greater capacity to increase the output voltage than the Boost converter. It was also found that the hybrid Boost converter has a low overshoot and a low ripple in the time response of its output signals. However, this converter is less efficient.